1982
DOI: 10.1104/pp.70.4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Proton-Translocating ATPase on Sucrose Gradients

Abstract: lonophore-stimulated ATPase activity and ATP-dependent quinacrine quench were enriched in parallel when microsomal vesicles were prepared from corn (Crow Single Cross Hybrid WF9-Mo17) roots and collected on a cushion of 10% dextran. Activities were highest in the apical 1.5 centimeters of the roots. Vesicles collected on the dextran cushion also contained NADH cytochrome c reductase (enriched in the apical 0.5 cm of the root) and nucleoside diphosphatase (distributed throughout the first four cm). On continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 19 publications
4
46
1
Order By: Relevance
“…In some systems, two populations of proton 21,22). This also seems to be the case for other groups working with corn (12,26), although recent work in our laboratory using a different variety of corn and a modified membrane isolation procedure has resulted in the identification of a second proton pump attributed to the Golgi (10). Our previous work with microsomal vesicles from corn coleoptiles demonstrated that the characteristics of the proton pump and the light density ofthe active vesicles were inconsistent with a plasma membrane, ER, Golgi, or mitochondrial origin (18,21,22).…”
Section: Resultsmentioning
confidence: 87%
“…In some systems, two populations of proton 21,22). This also seems to be the case for other groups working with corn (12,26), although recent work in our laboratory using a different variety of corn and a modified membrane isolation procedure has resulted in the identification of a second proton pump attributed to the Golgi (10). Our previous work with microsomal vesicles from corn coleoptiles demonstrated that the characteristics of the proton pump and the light density ofthe active vesicles were inconsistent with a plasma membrane, ER, Golgi, or mitochondrial origin (18,21,22).…”
Section: Resultsmentioning
confidence: 87%
“…Seeds of barley (Hordeum vulgare L. cv California Mariout 72) were sown on moist cheesecloth above aerated 0.5 mM CaSO4 and grown at 22°C in the dark for 7 …”
Section: Methodsmentioning
confidence: 99%
“…We compared the substrate specificity of three areas of the gradient and the I00,OOOg supernatant (Table II). The [6][7]. The activity of the fraction presumed to be rich in plasma membrane vesicles (fractions 10-13) was highly specific for ATP We compared the distribution of marker enzymes in 18-h gradients with the results from 2-h gradients (Figs.…”
Section: (16)mentioning
confidence: 99%
“…The following criteria strongly suggest a tonoplast origin of Recently, evidence has accumulated for the presence of two microsomal H+-ATPases in plants involved in the production of electrogenic H+ gradients (4,6,8,10, 11,18,19). One is associated with high density membranes (about 1.16-1.17 g/cm3 inhibited by vanadate and correlated with marker enzymes for plasma membrane (4,7,8,19).…”
mentioning
confidence: 99%